Analysis of Cases of Violence by Educators Against Students: A Case Study of SD N 4 Baito, South Konawe Regency (Decision Number 104/Pid.sus/2024/PN ADL) - Selvira Putri Oktaviani; Burham Pranawa; Ananda Megha Wiedhar Saputri (Regulate: Jurnal Ilmu Pendidikan, Hukum dan Bisnis, 2025)
This study addresses the issue of violence committed by educators against students, focusing on Court Decision Number 104/Pid.sus/2024/PN Adl involving Supriyani, an honorary teacher at SD Negeri 4 Baito, South Konawe Regency. The case presents a dilemma between disciplining students and the boundaries set by criminal law and child protection statutes. The aim of this research is to examine the legal considerations of the judges in reaching their verdict and to analyze the extent to which legal protection can be applied to teachers accused of violence. This study uses a normative juridical method with a qualitative descriptive approach, relying on secondary data such as statutory regulations, court decisions, and legal literature. The findings reveal that the panel of judges declared the defendant not legally and convincingly proven guilty. The legal reasoning was based on the weakness of the evidence, inconsistencies in child witness testimonies, and the absence of strong forensic medical proof. The research highlights the need for careful judgment in cases involving children as victims and teachers as defendants to prevent the misuse of legal instruments in criminalizing educators. Simultaneously, the protection of children remains a core priority within Indonesia’s legal system. These findings emphasize the urgency for clear ethical guidelines and regulatory frameworks for teachers to implement discipline without violating children's rights. This study is expected to serve as a reference for the development of educational law and the legal protection of educators in the future.